Evaluation of the accuracy of full-arch impressions between three different intraoral scanners and conventional impressions: A prospective in vivo study - Niharika Bhatia; Srirengalakshmi Muthuswamy Pandian (Tabriz University of Medical Sciences, 2024)
Background. This in-vivo study evaluated the accuracy of full-arch digital impressions obtained through different intraoral scanning technologies regarding trueness and efficiency against the standard alginate impressions. Methods. Alginate impressions were taken from 50 subjects, and the resulting stone casts were scanned using the Trios 3Shape desktop scanner. In-vivo scans were conducted on each participant using three intraoral scanners: Medit, CEREC Primescan, and 3Shape Trios. The scanned files were superimposed onto two software platforms: the 3Shape Orthoanalyser and Geomagic software. This superimposition was performed against the reference model to calculate 3D and 2D deviations, enabling efficiency comparisons between digital and traditional workflows based on work time in minutes. Measurements and comparisons were made in three planes: transverse, sagittal, and vertical dimensions for all the models and stone casts. Statistical analysis employed SPSS 23, with the significance level set at P<0.05. Results. Significant deviations were observed between the three intraoral scanners and the alginate impression, with molar and premolar areas showing greater imprecision across dental arches. Compared to the alginate technique, Medit i500 tended to reduce the transverse dimension in the areas mentioned above, while CEREC exhibited higher precision. Molar and premolar areas emerged as the regions with the greatest discrepancies, both in excess and deficiency, compared to the alginate impression. This difference in dimensions was, however, statistically insignificant overall. 3Shape Trios exhibited the shortest scan times, indicating higher efficiency. Among the intraoral scanners, Medit recorded the longest scanning duration. Conclusion. Accepting the null hypothesis, the scans obtained using all three scanners were comparable with statistically insignificant differences in the measurements. The three scanners differed in the total scan time taken, with the Medit scanner requiring the longest scan time and the 3Shape TRIOS 3 scanner demonstrating the shortest scan duration.